An update of the list of types of Ceraphronoidea, Cynipoidea and "Proctotrupoidea" (Hymenoptera) housed at the Museo de La Plata, Argentina - Díaz, Norma Beatriz (2005)
In this paper we listed and examined four type specimens of Ceraphronoidea, 94 of Cynipoidea and 198 of "Proctotrupoidea" (Hymenoptera) housed at the Museo de La Plata, Argentina (División Entomología) not included in previous papers. We also provide update information on categories of types, data of collection and hosts for all cases. These types belong to one, 10 and 12 species respectively and the species were described by Martínez (1), Diaz (2), Diaz & Gallardo (3), Gallardo, Diaz & Marchiori (1), Gallardo, Diaz & Uchoa (1), Kerrich & Quinlan (1), Pujade-Villar & Diaz (1), Ros-Farré & Pujade-Villar (1), De Santis & Loiácono (9), Loiácono (2), and Loiácono & Margaría (1).